2003
DOI: 10.1139/v03-127
|View full text |Cite
|
Sign up to set email alerts
|

The adsorption of cyclohexanone on aluminum oxide – hydroxide powders in relation to its electrocatalytic hydrogenation

Abstract: Henry's law constants were determined for cyclohexanone adsorption onto aluminium oxide – hydroxide powders by dynamic isotherm measurements using the HPLC method. The key parameters that control cyclohexanone adsorption were established. Further, it is suggested that the amount of cyclohexanone adsorbed onto aluminium oxide – hydroxide compounds (AOHC) is of paramount importance for its electrocatalytic hydrogenation in the presence of composite nickel–AOCH powders.Key words: adsorption isotherm, electrocatal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
12
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 16 publications
2
12
0
Order By: Relevance
“…The effect of the aluminate ion is more important in the supersaturated solution where the efficiency drops to less than 10%. Studies have shown that adsorption of organic molecules on the catalyst is a key parameter of ECH [14]. In situ modification of the catalyst surface by adsorption of molecules greatly influences the efficiency of ECH [19].…”
Section: Electrocatalytic Hydrogenation (Ech) Pathwaysmentioning
confidence: 99%
See 1 more Smart Citation
“…The effect of the aluminate ion is more important in the supersaturated solution where the efficiency drops to less than 10%. Studies have shown that adsorption of organic molecules on the catalyst is a key parameter of ECH [14]. In situ modification of the catalyst surface by adsorption of molecules greatly influences the efficiency of ECH [19].…”
Section: Electrocatalytic Hydrogenation (Ech) Pathwaysmentioning
confidence: 99%
“…This technique allows the testing of a broad family of catalysts in a short period of time. It was also possible to show a correlation between adsorption of the molecules on the catalyst and hydrogenation efficiencies [14].…”
Section: Introductionmentioning
confidence: 97%
“…Therefore, more emphasis is placed on improving the nature of the building material of the electrodes in order to increase ECH efficiency. A variety of materials have been developed; including: Raney Ni/Ni, Raney Ni/Hg pool, Pt/Pt, Pt/C, Rh/C [7], Pt/Pt and Pt/C with different concentrations of Pt [8]; different types of composite materials incorporated in reticulated vitreous carbon (RVC) like fractal nickel (Ni), crystalline nickel boride (Ni 2 B), and metallic nanoaggregates deposited on non-conductive powders like alumina, aluminum hydroxide, barium carbonate, and barium sulphate [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Competitive reactions such as production of molecular hydrogen can also take place (steps 5 or 6). Thus, in the case of supported electrocatalysts, the matrix (inorganic powder), which supports the metallic nanoaggregates and which monitors the adsorption of unsaturated molecules, was non-conductive until now [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…The most frequent aim of the adsorption investigation is the removal of arsenic ions from drinking water [16][17][18]. Only several publications deal with the adsorption of organic compounds [24,25] or drugs [26,27].…”
mentioning
confidence: 99%